A Feasibility Study on partially substituted Coarse Aggregate with Oil Palm Shell in Coconut Fiber Reinforced Concrete - Wee Ong, Siaw; Leong Lau, Teck; Wai Yeong, Tuck; Parvez Anwar, Mohammed; Elleithy, Wael (International Journal of Engineering and Technology, 2018)
In the search of alternative materials for the replacement of conventional coarse aggregate, the feasibility of utilizing agricultural waste products was looked into in the effort of producing a more environmentally friendly and less dense concrete. Mechanical properties of partially substituted coarse aggregates using oil palm shell (OPS) in a concrete composite reinforced with a low volume fraction of coconut fibre (CF) have been studied for its feasibility as an alternative solution to the problem. Analysis on the impact of compressive strength, flexural strength, density and Youngâ€™s modulus have been conducted on hardened coconut fibre reinforced concrete (CFRC) at 15% and 25% substitution by volume of conventional coarse aggregates with OPS. The properties of the composite concrete were evaluated with reference to the control sample, CFRC reinforced with 0.2% fibre volume fraction. The results have shown that it is feasible to produce a sustainable grade 30 concrete of lower density with CFRC at 25% level of OPS substitution.Â Â